Case studies on military law - Nilendra Kumar (New Delhi, 2011)
The first and the only book of its kind. It presents live cases relating to investigations and enquiries, disciplinary and administrative action decisions starting with hearing of charge, recording of evidence, issue of show cause notice, processing of pre-trial documents followed by disposal modes like summary trial, courts martial, award of censure and termination of service. Live cases have been cited to depict common pitfalls which are to be avoided. Process for award of maintenance, handling of human right cases, financial irregularities, audit objections, complaints and petitions, right to information, arbitration and Armed Forces Tribunal procedures have also been included. It has compiled relevant references for ready use. Will be invaluable for units and formations for correct and timely completion of pending matters. Of great help to officers preparing for promotion & competitive examinations and to counsels with practice in military law.
Keywords: Military law-Case studies